2018
DOI: 10.1111/jeb.13247
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic control of cold tolerance in the Glanville fritillary butterfly

Abstract: Thermal tolerance has a major effect on individual fitness and species distributions and can be determined by genetic variation and phenotypic plasticity. We investigate the effects of developmental and adult thermal conditions on cold tolerance, measured as chill coma recovery (CCR) time, during the early and late adult stage in the Glanville fritillary butterfly. We also investigate the genetic basis of cold tolerance by associating CCR variation with polymorphisms in candidate genes that have a known role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…However, as the cold-exposed individuals were unintentionally released into the enclosure at an older age and on warmer days, these results should be interpreted with caution. Interestingly, a previous study on the same system showed that cooler developmental conditions led to reduced cold tolerance in adults ( de Jong & Saastamoinen, 2018 ). However, we cannot say whether the potentially altered thermoregulation behaviour found here stems from a physical constraint (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…However, as the cold-exposed individuals were unintentionally released into the enclosure at an older age and on warmer days, these results should be interpreted with caution. Interestingly, a previous study on the same system showed that cooler developmental conditions led to reduced cold tolerance in adults ( de Jong & Saastamoinen, 2018 ). However, we cannot say whether the potentially altered thermoregulation behaviour found here stems from a physical constraint (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Experimental manipulations under more controlled conditions are also possible owing to the small size, high fecundity, and relatively short generation time of the species. Consequently, our understanding of the species includes knowledge of life history variation across development stages [ 4 , 5 ], dispersal dynamics [ 6 , 7 ], species interactions with host plants and parasitoids [ 8–12 ], and stress tolerance [ 13 , 14 ]. During the past decade, the system has also been used to study genetic and evolutionary processes, such as identifying candidate genes underlying variation and evolution of dispersal in fragmented habitats [ 15 ] and host plant preference [ 16 ], and assessing allelic variation and its dynamics in space and time [ 17–19 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…To gain a more complete understanding of the prospects and limitations of beneficial acclimation in buffering effects of temperature variation, a better understanding of the underlying mechanisms is important. At the mechanistic level, phenotypic plasticity in thermal tolerance may be caused by environmental effects on gene and protein expression or biosynthetic pathways [21, 22], but currently our understanding of the underlying mechanisms is very limited [15, 2327]. Recent developments in sequencing techniques though have opened up new opportunities to address this issue, enabling unbiased approaches by targeting entire genomes and transcriptomes [15, 28].…”
Section: Introductionmentioning
confidence: 99%